Planning the driverless city - Legacy, C.; Ashmore, D.; Scheurer, Jan; Stone, J.; Curtis, Carey (Routledge, 2019)
AV technologies have the potential to transform urban landscapes and existing transport systems and networks. Yet, the utopian imaginary of reduced automobile ownership and a new shared economic future sits in tension with suggestions that car dependency, urban sprawl and transport inaccessibility will be exacerbated. The issues are situated in a complex governance landscape involving an influential private sector who are increasingly setting the agenda. The public sector may be forced into reacting to the new innovations by information technology and automobile companies as they are introduced into existing built environments. Drawing on an extensive literature base and interviews with public sector planners, this paper reveals the conceptual gaps in the framing of AV technology – the prospects and limits – and how these are conceived. The paper raises questions about the role urban planning can play in the rollout of AVs in order to anticipate and mediate unwanted built environment and socio-spatial impacts, as well as reconciling the ambition of transport innovation with the public purpose of planning.